Alareef Rebelled Against Prince Abdulaziz Bin Saud 1908-1916 - Ali Abd Hammadi , Lect. Dr. (lark, 2022)
After Prince Abdul Aziz bin Abdul Rahman bin Faisal, whose nickname was "Ibn Saud", managed to restore the rule of the Al Saud family over Najd after he regained control of Riyadh in 1902, things did was not settle for him. Completely because he faced many problems,  One of the most prominent was the rebellion carried out. They were the grandsons of his uncle Prince Saud bin Faisal, whose known as "Al-Arayef". The rebellion took place during the period between 1908-1916. Thy Prince Abdul Aziz had to use the policy of Finally, he could end their rebellion completely in 1916, As a result, the affairs of government passed without a competitor to the branch of Abdul Rahman bin Faisal.
Keywords: Al-Arayef, Al Saud, Saudi Arabia, Abdulaziz bin Saud, Najd.